Energetics and electronic structures of perylene confined in carbon nanotubes - Nagasawa, Yuya (R Soc Open Sci, 2018)
The energetics and geometries of perylene encapsulated in carbon nanotubes (CNTs) have been investigated employing density functional theory using the generalized gradient approximation combined with the van der Waals correction. Our calculations show that the encapsulated perylene molecules possess two metastable molecular conformations with respect to the CNT wall, which are almost degenerate with each other. A standing conformation, with respect to the CNT wall, is the ground state conformation for a semiconducting (19,0)CNT, while a lying conformation is the ground state for a metallic (11,11)CNT. Cooperation and competition between perylene–perylene and perylene–CNT interactions cause these possible perylene conformations inside CNTs. However, the electronic structure of the CNT encapsulating the perylene molecules is found to be insensitive to the molecular conformation.